Virtual Monitoring as a Digital Delivery and Assessment Impact on Students' Learning - Pascal MUAM MAH; Iwona SKALNA; Uwakmfon Promise OFFIONG (Communications of International Proceedings, 2022)
In this paper, we identify the importance of certain measures for a smart, sustainable education and the assessment impact on student. By harnessing and harmonizing the creative, innovative potential of our students during COVID-19 as the peak of digitalization in history of education. Technological tools like ICT, IoTs, Big Data and Internet usage skills are specifically examine. In our today’s world of Digital era that has generated new functions for our societies and most importantly on old theories that were built on non-digital platform standards. It has been observed that online studies really fit in to the smart productivity and consumption pattern of our today’s era for students. This study identify areas that restructuring, should include in terms of tools like consumer-productivity need and effectiveness strategies. Sample questionnaires were run to ascertain student’s desire for online studies. It has been observed that interpersonal relationships is getting wider and more interesting desire for continuous digitalize education found amongst various learners. With the important aim of the study which is to see more machines to man than more men to machine as a tool to enhance quality education and ease in assessment of skills, pattern and tools for measuring effectiveness and satisfaction of knowledge acquired. In this paper, new solutions are proposed to keep the inclusiveness and connectivity amongst students and teachers.
Keywords: Virtual delivery & assessment impact; Digital education; ReMarkable Prototype Notebook & ICT Tools